2023
DOI: 10.1029/2022wr033913
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Pumping Controls Dissolved Organic Matter Properties and Outwelling From Mangrove Groundwater to Coastal Water

Abstract: Dissolved organic matter (DOM) in highly productive intertidal mangroves is an important carbon and nutrient source to the coastal ocean. In highly dynamic mangrove intertidal systems, both tidal pumping or geochemical factors can control DOM characteristics. The influence of groundwater flow on DOM properties and fluxes remains poorly understood. Here, we compared the concentrations, sources, and spectroscopic characteristics of DOM across a recharge‐discharge gradient. We used a three‐dimensional array sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Higher values indicate more aromatic, red‐shifted FDOM. The HIX was highest in the porewater samples where components C1 and C2 were enriched (Supporting Information Table S7) since microbial alteration increases humic‐like DOM in deeper aquifers of mangrove ecosystems (Xiao et al, 2023). Thus, increased HIX levels during low tide confirm the outwelling of a terrestrial DOM from mangrove porewater to the estuary.…”
Section: Discussionmentioning
confidence: 99%
“…Higher values indicate more aromatic, red‐shifted FDOM. The HIX was highest in the porewater samples where components C1 and C2 were enriched (Supporting Information Table S7) since microbial alteration increases humic‐like DOM in deeper aquifers of mangrove ecosystems (Xiao et al, 2023). Thus, increased HIX levels during low tide confirm the outwelling of a terrestrial DOM from mangrove porewater to the estuary.…”
Section: Discussionmentioning
confidence: 99%
“…Different tidal stages are associated with varying degrees of seawater-groundwater mixing, seawater infiltration, dissolved oxygen level, and microbial activity (Liu, Jiao, & Liang, 2018;Robinson, Li, & Barry, 2007). Recent studies showed that tidal pumping controls the properties of dissolved organic matter and nutrient concentration in coastal aquifers (Liu et al, 2017;Xiao et al, 2023). These variations may lead to changes in the (bio)geochemical processes and rates related to trace metals in coastal aquifers.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%